Impact of climate change and extension service on rice farmers' yield in Ebonyi State, Nigeria (Asian Journal of Agriculture, 2024)
Abstract. Emmanuel OE, Nkiruka B-CG, Nnenna OM, Ojoko NIU, Chinenyenwa T-AA, Ada AB, Oluwakemi OI, Thankgod EK, Oscar OI, Nnabugwu UB, 2024. Impact of climate change and extension service on rice farmers' yield in Ebonyi State, Nigeria. Asian J Agric 8: 116-123. The study examined the impact of climate change and extension service on rice farmers' yield in Ebonyi State, Nigeria. A total of 402 rice farmers were sampled through multi-stage sampling for questionnaire administration. Primary data collected were analyzed using mean, frequency, percentage, ordinary least square multiple regression techniques, the Local Average Treatment Effect (LATE) model, and the probit model. Socio-economic characteristics show that a greater proportion of the farmers were male (51.7%), married (84.1%), and attended secondary education (47.8%). Sources of climate change information were farmer-to-farmer (100%), telephone/mobile phone (98.5%), radio (92.5%), workshop/seminars (73.4%), and television (46.8%). Temperature (P
Keywords: Climate change, extension service, impact, rice farmers, yield